2020
DOI: 10.1002/jsfa.10901
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence of Alternaria mycotoxins in wheat and potential of reducing associated risks using magnolol

Abstract: BACKGROUND Wheat is one of three major food crops in China. Alternaria species can cause spoilage of wheat with consequent mycotoxin accumulation. Alternariol (AOH), alternariol monomethyl ether (AME), and tenuazonic acid (TeA) are the most common and frequently studied mycotoxins. There are limited regulations placed on Alternaria mycotoxin concentrations worldwide due to the lack of toxicity data available. More data on the levels of mycotoxin contamination are also needed. It is also important to reduce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 39 publications
5
21
0
5
Order By: Relevance
“…However, our study demonstrated the significant abundance of A. sect. Infectoriae fungi in grain in the Urals and West Siberia regions, which is consistent with the recent results of a mycological analysis of grain grown in these regions [34].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, our study demonstrated the significant abundance of A. sect. Infectoriae fungi in grain in the Urals and West Siberia regions, which is consistent with the recent results of a mycological analysis of grain grown in these regions [34].…”
Section: Discussionsupporting
confidence: 91%
“…Recently, the predominance of Alternaria mycotoxins (mainly TEN) in grain samples from the Urals and Siberia region of Russia has also been shown [14,36]. In our study, TeA and TEN were found more often than AOH and AME in the grain samples from both regions, which corresponds to previous reports indicating these Alternaria mycotoxins are the most common in grain grown in Asia [22,34].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations